COVID-19 as an Immune Complex Hypersensitivity in Antigen Excess Conditions: Theoretical Pathogenetic Process and Suggestions for Potential Therapeutic Interventions - Manzo, Giovanni (Frontiers in Immunology, 2020)
Because of particular properties of SARS-Cov-2, such as an high infection speed, its antigenic nature, evolutionarily unknown to the human immune system, and/or a viral interference on the immune response mechanisms, this virus would determine in the subjects a delayed anomalous (slow and /or low) immune response, ineffective and, finally, self-damaging. The hypothetical pathogenetic process for covid-19 could occur in three phases: a) Viral phase, asymptomatic or weakly symptomatic, with an a-specific innate immune response; b) Immunological phase, intermediately symptomatic, with an anomalous specific immune response (delayed, slow and/or low synthesis of IgM and IgG) in antigen excess conditions, immune complex formation and complement activation with tissue damages; c) Haemo-vascular phase, severely symptomatic, where complement-mediated tissue damages would induce vascular inflammation and systemic alteration of the coagulation homeostasis. This hypothesis is well supported by the immune-histochemical and microscopic demonstration in severe patient lungs of co-localized spike viral proteins, terminal components of the activated complement system (C5b-9 membrane attack complex) and microvascular deposits of small fibrin thrombi. This picture could be aggravated by the involvement of neutrophils and macrophages, releasing additional lytic and inflammatory factors. Thus, covid-19 would arise as a simple viral infection, develop as a diffuse immune complex hypersensitivity and explode as a systemic haemo-vascular pathology. If this hypothesized process would be real, suitable therapeutic interventions might be carried out, able to interfere with or block the critical factors in the various phases.